Factors Influencing on Consumers’ Decision Making in Purchasing Drug Coated Balloon - Chaichitaton, Kanisorn (Ph.D. in Social Sciences Journal, 2018)
The objectives of the study are to 1) identify and analyze the factors that influence consumers’ decision making in purchasing drug-coated balloon in Bangkok, Thailand. 2) further provide recommendations for people related to the medical devices industry and recommendations for further research and 3) use the results for company’s marketing plans to introduce the Drug-Coated Balloon to Thai market. The target group of this research are patients, who has Peripheral artery disease (PAD) living in Bangkok. There are a total of 225 hospitals to maintain the right proportion of public and private hospitals in different area of Bangkok and choose total 8 hospitals form the northern, southern, eastern, and western part of Bangkok from a total of 253 patients. The questionnaires composed of 4 sections, which are demographic background, marketing mix, health conditions, and consumers’ decision making. For the demographic factor the results show that from all 7 demographic factors there are 4 factors (57%) that the results show to have relationship with consumers’ decision making in purchasing drug coated balloon, which are, age, education, reimbursement, and income. For marketing mix factors the results show that all 4 marketing factors don’t have relationship with consumers’ decision making in purchasing drug coated balloon. For health conditions factors from all 5 factors only duration of illness and other disease factor (40%) have an influence to consumers’ decision making in purchasing drug coated balloon.